2010
DOI: 10.1002/hec.1689
|View full text |Cite
|
Sign up to set email alerts
|

Information asymmetry and performance tilting in hospitals: a national empirical study

Abstract: Information asymmetry offers hospitals an advantageous position in achieving profit maximization. The study also documented the presence of performance tilting by health-care management. Whether increased information demands from a society accustomed to significant disclosure will reduce this agency problem is not yet clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…This suggests that the healthcare reform policy may not achieve the initial goal for reducing health care costs, and that failure to manage potential conflicts of interest among different sectors and stakeholders may undermine health policy [ 22 ]. Indeed, information asymmetry among medical industry, health care providers, and consumers may cause inappropriate prescriptions and overuse of medical services, which may place health care providers and pharmaceutical industry in an advantageous position to maximize profit [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the healthcare reform policy may not achieve the initial goal for reducing health care costs, and that failure to manage potential conflicts of interest among different sectors and stakeholders may undermine health policy [ 22 ]. Indeed, information asymmetry among medical industry, health care providers, and consumers may cause inappropriate prescriptions and overuse of medical services, which may place health care providers and pharmaceutical industry in an advantageous position to maximize profit [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, information sharing and acquisition is a transaction cost [ 59 , 60 ] in which some health care providers may not decide to invest. As a fundamental peculiarity in health care [ 61 ], asymmetric information remains in this Internet age and continues to affect the effectiveness and efficiency of care [ 62 ]. To deliver improved care and to enhance patient benefits, systematic research that examines the effective schemes of promoting medical information sharing and exchange involving IT, behavioral and social sciences, and other disciplines should be prioritized.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that information asymmetry presents challenges to the marketisation of public services (e.g. Wang et al ., ) and, in discussions of higher education, Del Ray () uses the term in its broadest sense to refer not only to asymmetry between buyer and seller, but also between different types of buyer.…”
Section: Information Asymmetrymentioning
confidence: 99%